The Influence of Trading Halts and Financial Performance on the Composite Stock Price Index (JCI) in Manufacturing Companies Listed on the Indonesia Stock Exchange. - Alfiani; Suci Triwardani (IECON: International Economics and Business Conference, 2025)
This study aims to analyze the influence of trading halts and financial performance on the Indonesia Composite Index (JCI) in the Indonesia Stock Exchange (IDX). Trading halts are mechanisms implemented to temporarily suspend stock trading during sharp market declines, with the goal of maintaining market stability and protecting investors. Using a quantitative approach with multiple linear regression analysis, this research examines secondary data from financial reports of manufacturing companies listed on the IDX from 2020 to 2025. The findings reveal that neither trading halts nor financial performance have a statistically significant impact on the JCI, with significance values exceeding the 0.05 threshold. These results align with prior studies suggesting that external and macroeconomic factors play a more substantial role in stock market movements than internal corporate variables. The study also identifies research gaps, emphasizing the need to explore additional variables that may influence the JCI. The implications of this research provide valuable insights for investors and policymakers in making informed investment decisions, while also highlighting opportunities for future studies to enhance understanding of stock market dynamics in Indonesia. Future research could benefit from incorporating macroeconomic indicators, monetary policies, and investor sentiment, as well as employing longitudinal and mixed-method approaches for a more comprehensive analysis.